Perbedaan Persepsi terhadap Kesetaraan Gender pada Siswa SMA Sekolah Heterogen dan Homogen - Della Puspita Sari Sembiring; Yohanes Heri Widodo (Concept: Journal of Social Humanities and Education, 2024)
This study aims to determine; (1) differences in perceptions of gender equality among high school students in co-education and single sex education; (2) How high is the perception of gender equality among high school students in co-education, single sex education for girls and single sex education for boys; (3) How many items on the gender equality scale are identified as not optimal. This study uses a comparative quantitative approach. The subjects of the study were 113 high school students in co-education schools, 121 high school students in single sex education schools for boys, and 111 high school students in single sex education schools for girls. The results of the study indicate that; 1) There are significant differences between high school students in co-education , single sex education schools for girls and single sex education schools for boys; 2) The level of perception of gender equality among high school students in co-education schools has a result of 57% in the very high category, 43% high, 5% moderate and 0% in the low and very low categories; 3) The level of perception of gender equality among high school students in single sex education schools for girls has a result of 86% in the very high category, 14% high, 1% moderate and 0% in the low and very low categories; 4) The level of perception of gender equality among high school students in single sex education schools for boys has results of 22% in the very high category, 52% high, 21% moderate and 0% in the low and very low categories.